Discussion of a Well-Designed Clinical Trial Which Did Not Demonstrate Effectiveness: UIC Center for Botanical Dietary Supplements Research Study of Black Cohosh and Red Clover - Shulman, Lee P. (Fitoterapia, 2010)
The performance of a clinical trial for pharmaceutical agents is usually undertaken only after there is likely benefit demonstrated from the use of the putative agent. The consideration of botanical products as pharmaceutical agents must similarly go through a rigorous evaluation process. The present work reviews the recently published Phase II study evaluating the effectiveness of black cohosh and red clover in a randomized trial with conjugated equine estradiol/medroxyprogesterone acetate and placebo for the treatment of menopausal symptoms. We analyze the possible reasons why this study failed to show benefit for either botanical product in reducing menopause-related vasomotor symptoms.